Use of phenolic resin in coke making at Tata Steel. (9th August 2017) - Nag, D.; Das, B.; Dash, P. S.; Sen, S.; Paul, S.; Verma, S.; Haldar, S. K.
Abstract : Quality of coke is very much important for blast furnace productivity. Phenol-formaldehyde resin can be used as an additive in small quantity in the coal blend for improvement of coke quality. It enhances the fluidity of coal blend during co-pyrolysis with coal and hence improves the coke quality. After successful lab-scale study, this phenomenon has been demonstrated in top charge battery and heat-recovery oven of Tata Steel through plant trial. It was found that 0.3–0.4% addition of phenolic resin in the coal blend improves coke quality.